Le patrimoine des écoles d’art aujourd’hui - Amel Nafti; Morwena Joly-Parvex (In Situ)
Interview with Amel Nafti, Managing Director of the école supérieure d’Art et de Design of Grenoble and Valence-ESAD Grenoble Valence since 2018. She mentions her work on the prints and artist’s editions collected and owned by the villa Arson, when she was Head of the Library and then Director of Studies and Research there. Today, she considers that the school history is an integral part of the school plan she is managing. She is coordinating with Pierre Oudart a working group devoted to the history of art schools within the Association of art schools, the ANDEA network.